A Comprehensive Survey of Neighborhood-Based Recommendation Methods used in E-Learning Recommender Systems - Saul Nicholas, J; Sagayaraj Francis, F (International Journal of Computer Sciences and Engineering, 2019)
This paper presents the essentials of the background, available literature and technologies presently available in e-leaning specifically recommender systems and its range of applications, different techniques used for the general recommender systems, e-learning recommender systems and the specific neighborhood-based recommender methods used. A comprehensive survey has been carried out to elucidate the types of neighborhood-based recommendation methods used in e-learning recommender systems. The paper highlights these methods with an comparative analysis of the recommendation methods.